7S-Based Feeding and Its Impact on the One Health Approach and Human Development in Latin America: An Integrative Review - Benny Andrade-Arita; Ma. Sandra Hernández-López; Gilberto Herrera-Ruiz; Juan Fernando García-Trejo; Humberto Aguirre-Becerra; Adriana Rojas-Molina; Juvenal Rodríguez-Reséndiz (Societies, 2025)
This article presents an integrative review of the role of the 7S-Based Feeding framework (Healthy, Sustainable, Safe, Social, Sovereign, Solidary, and Satisfactory) and its relationship with the One Health approach and human development in Latin America. Through an analysis of 18 articles selected via the PRISMA methodology and coded using ATLAS.ti, thematic patterns and analytical gaps were identified using Sankey diagrams and qualitative content analysis. The results indicate that the dimensions most frequently addressed were Sustainable, Healthy, Safe, and Social. In contrast, the Sovereign and Solidarity-based dimensions were underrepresented, while the Satisfactory dimension was entirely absent. Only one-third of the articles explicitly applied the One Health framework. The study proposes a theoretical integration of these approaches to enhance the understanding of food systems as determinants of well-being. It concludes that incorporating the 7S-Based Feeding framework into public food policies could strengthen their impact on equity, health, and resilience in Latin American communities.